Prenatal ultrasound diagnosis and prognosis assessment of fetal neck masses - Zhang, Peipei; Wu, Xining; Ouyang, Yunshu; Yang, Tianrui; Zhang, Yixiu; You, Hui; Lv, Yan; Jiang, Yulin; Dai, Qing; Meng, Hua (Frontiers in Pediatrics, 2025)
ObjectiveThis study retrospectively analyzed the prenatal ultrasound features and outcomes of fetal neck masses to improve the understanding of fetal neck masses and provide evidence for prenatal consultation, prognosis assessment, delivery mode selection, and clinical intervention.MethodsFrom January 2018 to November 2023, 18 patients who underwent routine prenatal ultrasonography in the ultrasound department of Peking Union Medical College Hospital or who were referred to our hospital for the diagnosis of a fetal neck mass were retrospectively identified. Their prenatal ultrasound characteristics and pregnancy outcomes were examined and follow-up was conducted.ResultsThere were 18 cases of fetal neck masses. The mean gestational age at which the fetal neck mass was first detected was 27 ± 6 weeks (range 17–38 weeks). There were seven (39%) male fetuses, nine (50%) female fetuses, and two (11%) fetuses of undetermined sex. The clinical diagnosis was lymphangioma in 14 cases (78%), hemangioma in two (11%), teratoma in one (6%), and congenital goiter in one (6%). The maximum diameter of the fetal neck mass at the first ultrasound examination was 1.8–8.6 cm, and the median diameter was 4.3 (2.5, 6.5) cm. The median mass volume was 17.0 (3.5, 59.0) cm3 (range 1.0–219.0 cm3). The neck mass was cystic in nine cases, a cystic solid mass with compartmentalization in five cases, and a solid mass with a blood flow signal in four cases. Sixteen fetuses were delivered by elective cesarean section, while two were born via induced labor. The average postnatal follow-up time was 27 months, and the longest follow-up was 6 years. There were 13 cases (72%) with a favorable outcome and five (28%) with an unfavorable outcome.ConclusionA fetal neck mass is a rare benign lesion. Accurate evaluation of the size and location of the cervical mass by prenatal ultrasound, auxiliary examinations such as magnetic resonance imaging, and assessments of clinical manifestations and related complications are crucial for appropriate prenatal consultation, prognosis assessment, delivery mode selection, and postpartum management. Multidisciplinary treatment is essential for the successful management of fetal cervical masses.